Study on effect of toluene-acid treatments of recycled carbon black from waste tyres: physico-chemical analyses and adsorption performance - Nur Alia Sahira Azmi; Kam, Sheng Lau; Siew, Xian Chin; Sarani Zakaria; Shahariar Chowdhury; Chin, Hua Chia (Penerbit Universiti Kebangsaan Malaysia, 2023)
Recycled carbon black (rCB) produced by pyrolysis has a low value because it contains high levels of impurities, such as sulfur, nitrogen, and oxygen. Various treatments have been proposed using chemicals to purify and improve the properties of rCB. In this study, rCB was treated with toluene (rCB-T), followed by subsequent treatment using acids HCl (rCB-T-HCl), HNO3 (rCB-T-HNO3 ), and HCl-HNO3 (rCB-T-HCl-HNO3 ). The treated rCB samples were characterized using CHNS analyser, scanning electron microscope, BET analyser, zeta potential, Fourier transform infrared spectroscopy, and Raman spectroscopy. The adsorption of methylene blue dye onto the rCB samples was also investigated to study the effectiveness of the treatments. Treatment with toluene alone was insufficient to increase the carbon content and surface area of the rCB. Subsequent treatment of rCB with acids, especially HNO3 , significantly increases the carbon content, surface area, surface functional groups, and surface charge of the rCB. This results in an increased adsorption capacity of the rCB, from 6.04 mg/g to 46.51 mg/g for the rCB-HNO3 and 54.80 mg/g for the rCB-T-HCl-HNO3 .